ZOO INDONESIA: SUATU STUDI INFORMETRIKA - Nurhayati, Muthia (BACA: Jurnal Dokumentasi dan Informasi, 2016)
This study aims to determine the development of Tropical Fauna Journal Zoo Indonesia which includes article distribution, patterns of authorship and fauna research subject at issue in 1983-2014. This study uses informetricsanalysis of all articles in the journal. The results showed: (1) the distribution of articles on every volume published by Zoo Indonesia have increased with the last number is six articles on each volume to its publication; (2) authorship patterns show the dominant by single author of 46,08%; and (3) research subjects that most discussed is about arthropods amounted to 30,41%. The conclusion is Zoo Indonesia on his way continuously tries to improve its quality as a scientific journal by a system of e-journal and also continue to fix both physically and editorial system aspects in it.